Pemanfaatan Limbah Rambut Manusia dan Penambahan H2o2 Untuk Pengolahan Oli Mesin Clipper - Gatot Prio Anggoro; Endi Adriansyah; Asih Suzana; Marhadi Marhadi (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
Waste lubricating oil from hair clipper machines generated by barbershop activities is a hazardous liquid waste containing oil and grease, suspended solids, and can alter the pH of aquatic environments if left untreated. This study aims to analyze the effectiveness of utilizing human hair waste as an adsorbent combined with the addition of hydrogen peroxide (H2O2) in improving the pH parameter of clipper engine oil waste. The research used an experimental method with a Magnetic stirrer at adsorbent weight variations of 5 g, 10 g, and 15 g and contact times of 30, 60, and 90 minutes. The results showed that the initial pH of 6.37 changed after treatment. The condition closest to neutral was obtained at the 10 g variation with a 30-minute contact time, namely pH 6.96 (9.26% efficiency), while the 5 g weight tended to raise the pH to alkaline (pH 8.48) and the 15 g weight lowered the pH to more acidic (pH 6.14). For the Total Suspended Solids (TSS) parameter, the initial value of 3,282.08 mg/L decreased significantly after treatment, with the lowest result at 5 g and a 60-minute contact time, namely 334.16 mg/L (89.82% efficiency). The addition of H2O2 played a role in the oxidation process affecting the pH stability of the treated waste.